The Effect of Supply Chain Management And Warehouse Management On The Productivity of Msme Rice Milling In Kedungwaringin District, Bekasi Regency - Pahni Irfansah; Andi Heru Susanto (Journal of Social Science, 2024)
The discussion on the issue of the global food crisis presented by the Minister of Agriculture of Indonesia at the G20 interstate meeting has created polemics in Indonesia. Nonetheless, Indonesia is said to be able to face the global food crisis that will hit. To realize this statement, a good supply chain management and warehouse management system is needed. Therefore, research will focus on the use of supply chain management and warehouse management to determine the effect on productivity during a crisis with PB research as the subject. Sri Bagja Mekarjaya as one of the MSME businesses in the Kedungwaringin sub-district. This research uses a quantitative approach with a sample of 80 respondents using a questionnaire. Instrument testing includes validity and reliability tests with the CFA measurement model. Data analysis used descriptive analysis, while hypothesis testing used the F/Simultaneous Test. The results showed that (1) supply chain management had a positive and significant effect on productivity (2) warehouse management had a positive and significant effect on productivity (3) supply chain management had no positive and significant effect on warehouse management. This research was only conducted on rice milling businesses in Kedungwaringin District